Polyaniline-based carbon nanospheres and redox mediator doped robust gel films lead to high performance foldable solid-state supercapacitors. (27th July 2017) - Feng, Enke; Peng, Hui; Zhang, Zhiguo; Li, Jindan; Lei, Ziqiang
Abstract : As-fabricated foldable solid-state supercapacitors are suitable for highly fold-tolerant high-energy-density energy storage device applications. Abstract : A novel and high-performance foldable solid-state supercapacitor has been developed based on nitrogen-containing polyaniline-based carbon nanosphere (C-PANI) coated carbon cloth electrodes and the AQSA-Na (anthraquinone-2-sulfonic acid sodium salt) redox mediator doped PVA (polyvinyl alcohol)–H2 SO4 robust gel film electrolyte. The foldable solid-state supercapacitor demonstrates outstanding electrochemical performance such as a large specific capacitance of 430 F g −1 at a current density of 0.8 A g −1, a remarkably high energy density of 33.4 W h kg −1 at a power density of 600 W kg −1 and excellent cycling stability with 90% specific capacitance retention after 1000 cycles. Simultaneously, the high flexibility of the as-fabricated solid-state supercapacitor enabled it to work under both normal and folding conditions, and the device could be folded/unfolded repeatedly up to 500 times with only a small capacitance loss of 9%. These results indicate that the as-fabricated solid-state supercapacitor is suitable for highly fold-tolerant high-energy-density energy storage device applications. More importantly, owing to the solid-state and integrated configuration, several supercapacitors can be conveniently interconnected together in series or parallel to improve the output potential or current.